Dual-tagging Gene Trap of novel genes in Drosophila melanogaster. - Lukacsovich, T.; Asztalos, Z.; Awano, W.; Baba, K.; Kondo, S.; Niwa, S.; Yamamoto, D. (Genetics, 2001)
A gene-trap system is established for Drosophila. Unlike the conventional enhancer-trap system, the gene-trap system allows the recovery only of fly lines whose genes are inactivated by a P-element insertion, i.e., mutants. In the gene-trap system, the reporter gene expression reflects precisely the spatial and temporal expression pattern of the trapped gene. Flies in which gene trap occurred are identified by a two-step screening process using two independent markers, mini-w and Gal4, each indicating the integration of the vector downstream of the promoter of a gene (dual tagging). mini-w has its own promoter but lacks a polyadenylation signal. Therefore, mini-w mRNA is transcribed from its own promoter regardless of the vector integration site in the genome. However, the eyes of flies are not orange or red unless the vector is incorporated into a gene enabling mini-w to be spliced to a downstream exon of the host gene and polyadenylated at the 3' end. The promoter-less Gal4 reporter is expressed as a fusion mRNA only when it is integrated downstream of the promoter of a host gene. The exons of trapped genes can be readily cloned by vectorette RT-PCR, followed by RACE and PCR using cDNA libraries. Thus, the dual-tagging gene-trap system provides a means for (i) efficient mutagenesis, (ii) unequivocal identification of genes responsible for mutant phenotypes, (iii) precise detection of expression patterns of trapped genes, and (iv) rapid cloning of trapped genes.